Mpox in India: Current Insights and Strategic Recommendations - Tulika Singh; Sanju Sharma (Indian Journal of Community Medicine)
Mpox, formerly known as monkeypox, has gained significant attention globally due to recent outbreaks, particularly the emergence of the Clade 1b strain. The World Health Organization declared a Public Health Emergency of International Concern in August 2024, emphasizing the need for robust public health responses. In India, the first case of Clade 1b was reported in September 2024, highlighting the urgent requirement for enhanced preparedness. This article examines the current landscape of Mpox in India, discussing its epidemiology, public health measures, and the challenges faced in controlling the spread of the disease. Key challenges include stigmatization of affected populations, resource limitations in healthcare infrastructure, and the necessity for early detection and public awareness. To address these challenges, recommendations are proposed, focusing on community engagement, strengthening surveillance systems, fostering international collaboration, and implementing effective crisis communication strategies. A coordinated response involving multiple sectors is crucial to combat Mpox and protect public health in India. By adopting a comprehensive approach, India can enhance its resilience against Mpox and similar public health threats.